If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + 12 = -177 Reorder the terms: 12 + 9x = -177 Solving 12 + 9x = -177 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + 9x = -177 + -12 Combine like terms: 12 + -12 = 0 0 + 9x = -177 + -12 9x = -177 + -12 Combine like terms: -177 + -12 = -189 9x = -189 Divide each side by '9'. x = -21 Simplifying x = -21
| 9/25w^4+w^2z^3+1/9z^6 | | 2x/5-x/2 | | -1x+15+3x+15=-4 | | x(9x-5)=13 | | -5a-10=10 | | 0.12(y-7)+0.04y=0.10y-0.9 | | x(x+2)-3x=4+y | | (2/3)x-(1/6)=(1/2)x+(5/6) | | 9r+5=4r+5 | | n+n+2+n+4+n+6+n+8=1095 | | -7x=175 | | n+n+1+n+2+n+3=60 | | 4[2x-(3-x)+5]=-7-2 | | 9x-20-61+13x=17x+57-14x+71 | | 20d+12-12d=-43 | | 1/4=-1/85/4X | | 6k^2+13k-5a^2=0 | | 22=-11r | | 1/16=-x/11 | | -3+p=7 | | 4/11-6 | | -3+p= | | 4/5x-6=5 | | 6*5+4*10=10c | | (5/2)t-t=3+(3/2)t | | (-2/3)t-3=-5 | | 7x+4=7(x+2) | | n+n+2+n+4=126 | | 36x^2-75m^2=0 | | 3p/5+10=16 | | 4(x+4)/3=3x-2 | | y=-7.36(315)-14354.33 |